Developing a Roadmap for Mass Vaccination of COVID-19 in Iran: A Qualitative Study. (16th November 2023) - Seyedin, Hesam; Dowlati, Mohsen; Barzegar, Mohammad; Bahramzadeh, Saeid; Khanizade, Abed; Roshanravan, Mostafa; Adibi, Haleh; Barghi-Shirazi, Fahimeh; Rouhollahi, Mahboubeh
Abstract: Background: Nowadays, the Covid-19 pandemic is 1 of the most important challenges worldwide, especially in terms of health. The most important strategy to prevent and control the Covid-19 pandemic is mass vaccination. This study aimed at developing a roadmap for the mass vaccination of COVID-19 in Iran. Methods: The current study was conducted using a qualitative approach with a content analysis method. In the first step, the review of literature and documents was carried out by a search in scientific databases. In the next step, the data were amassed via in-depth and semi-structured interviews with experts who were selected purposefully, including policymakers, health care workers, and managers. After this, 3 multidisciplinary expert panels for roadmap development were held. Results: Based on the literature review, interviews, and 3 stages of an expert panel, the final roadmap was developed with 5 dimensions. These included outcomes, planning and preparation, strategies, and preparation, implementation, monitoring, and evaluation. Conclusions: This roadmap was developed to improve mass vaccination during the COVID-19 pandemic. According to our findings, it is strongly recommended that the vaccination roadmap with all the above-mentioned features and comprehensive structure should be applied to mitigate the consequences of the COVID-19 pandemic.